PEMBENTUKAN KARAKTER MELALUI PEMBELAJARAN PPKN DENGAN PERSPEKTIF BEHAVIORISME - Dhara Ayu Restuning Tyas Dhara; Supriyono (LPPM Universitas Muhammadiyah Bulukumba, 2024)
The purpose of this study is to analyze character development through civic education with standard grade X material from a behavioral science perspective. This research uses descriptive method with qualitative approach. The topic of the research paper is the learning of class X students of SMK Negeri 7 Semarang. Data collection used observation, interview and documentation techniques. Miles and Huberman interactive model analysis technique was used for data analysis. The results show that the application of behaviorism theory shows that students can build knowledge based on their experiences that are reflected in their personal behavior. Teachers, departments and of course school support are responsible for the implementation of learning activities. This learning is done in an interesting, challenging and fun way. The activity is a character representation that consists of learning activities that aim to shape students into characters that affect their daily lives.